The Role of Grifola frondosa Polysaccharide in Preventing Skeletal Muscle Atrophy in Type 2 Diabetes Mellitus - Ying She; Yun Ma; Pei Zou; Yang Peng; Yong An; Hang Chen; Peng Luo; Shaofeng Wei (Life, 2024)
Type 2 diabetes mellitus (T2DM) is a burgeoning public health challenge worldwide. Individuals with T2DM are at increased risk for skeletal muscle atrophy, a serious complication that significantly compromises quality of life and for which effective prevention measures are currently inadequate. Emerging evidence indicates that systemic and local inflammation stemming from the compromised intestinal barrier is one of the crucial mechanisms contributing to skeletal muscle atrophy in T2DM patients. Notably, natural plant polysaccharides were found to be capable of enhancing intestinal barrier function and mitigating secondary inflammation in some diseases. Herein, we hypothesized that Grifola frondosa polysaccharide (GFP), one of the major plant polysaccharides, could prevent skeletal muscle atrophy in T2DM via regulating intestinal barrier function and inhibiting systemic and local inflammation. Using a well-established T2DM rat model, we demonstrated that GFP was able to not only prevent hyperglycemia and insulin resistance but also repair intestinal mucosal barrier damage and subsequent inflammation, thereby alleviating the skeletal muscle atrophy in the T2DM rat model. Additionally, the binding free energy analysis and molecular docking of monosaccharides constituting GFP were further expanded for related targets to uncover more potential mechanisms. These results provide a novel preventative and therapeutic strategy for T2DM patients.